Nonequilibrium phase transition with gravitational-like interaction in a cloud of cold atoms - Barré, J. (2014)
We propose to use a cloud of laser-cooled atoms in a quasi-two-dimensional trap to investigate a nonequilibrium collapse phase transition in the presence of a gravitational-like interaction. Using theoretical arguments and numerical simulations, we show that, like in two-dimensional gravity, a transition to a collapsed state occurs below a critical temperature. In addition and as a signature of the nonequilibrium nature of the system, persistent particle currents, dramatically increasing close to the phase transition, are observed.